Indus Cricket Academy Limited : constructing the financial statements - Agarwalla, Sobhesh Kumar, (SAGE business cases., 2020)
Three former cricket players started a Cricket academy. To expand the business, they registered the firm as a public limited company. Membership fees and rental incomes from facilities owned/leased by the company generated the main revenues of the firm. The academy is doing great as some of the good players trained in the academy are representing their states and zonal teams in reputed domestic cricket leagues.The case can be used to discuss the accounting mechanism, including the preparation of the financial statements. It also provides an opportunity to prepare the financial statements directly from the opening balance sheet and a summary of the transactions entered during an accounting period. It can also be used as an exam case for the first accounting module.